Ultrasound-assisted immunotherapy for malignant tumour - Cai, Xiaowen; Liu, Yujie; Luo, Guosheng; Yu, Zhanwang; Jiang, Cheng; Xu, Chuanshan (Frontiers in Immunology, 2025)
Malignant tumour represents a significant global public health concern. The advent of immunotherapy has brought about a revolutionary shift in the landscape of tumour treatment, offering a ray of hope to patients across the globe. Immunotherapy strategies have demonstrated considerable promise in clinical trials. However, the immunosuppressive environment within the tumour microenvironment has constituted a significant obstacle to the advancement of immunotherapies. It is therefore imperative to develop more efficacious and personalised approaches. The utilisation of non-invasive ultrasound-assisted immunotherapy represents a promising strategy. Ultrasound has the capacity to induce an immune response and stimulate other drugs to achieve a specific response, thereby reducing the toxic side effects of treatment and enhancing the outcome of immunotherapy. This paper presents a systematic introduction to the various mechanisms related to ultrasound and reviews the recent advancements of ultrasound-assisted tumour immunotherapy, including ultrasonic ablation, combined application with contrast agents, and sonodynamic therapy.